2007
DOI: 10.1007/s10956-007-9051-9
|View full text |Cite
|
Sign up to set email alerts
|

How Much Have They Retained? Making Unseen Concepts Seen in a Freshman Electromagnetism Course at MIT

Abstract: The introductory freshmen electromagnetism course at MIT has been taught since 2000 using a studio physics format entitled TEAL-Technology Enabled Active Learning. TEAL has created a collaborative, hands-on environment where students carry out desktop experiments, submit web-based assignments, and have access to a host of visualizations and simulations. These learning tools help them visualize unseen electromagnetic concepts and develop stronger intuition about related phenomena. A previous study has shown tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 25 publications
3
35
0
3
Order By: Relevance
“…The control group participants required a higher cognitive effort to learn and solve problems that required visualization whereas the experimental group had better opportunities to understand the combined behavior of electromagnetic forces. The findings of the current study extend those of Dori et al (2007) who found that students improved learning outcomes through the use of visualization in a web-based course. Further studies with a larger data sample are necessary to identify the causes of learning effectiveness of the AR-based application over the web-based application.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The control group participants required a higher cognitive effort to learn and solve problems that required visualization whereas the experimental group had better opportunities to understand the combined behavior of electromagnetic forces. The findings of the current study extend those of Dori et al (2007) who found that students improved learning outcomes through the use of visualization in a web-based course. Further studies with a larger data sample are necessary to identify the causes of learning effectiveness of the AR-based application over the web-based application.…”
Section: Discussionsupporting
confidence: 85%
“…Unlike what happens in other Physics' conceptual areas, when dealing with electromagnetism, students' mental models should include abstractions and invisible factors for which students have no reallife references (Maloney, O'Kuma, Hieggelke, & Van Heuvelen, 2001). The relevance of presenting learning materials not only through words but also through visual assets to fully understand the nature of scientific phenomena and processes was reported by Dori, Hult, Breslow, and Belcher (2007). Indeed, these concerns were already addressed in the MIT Technology Enabled Active Learning (TEAL)/Studio Project where students developed much better intuition about, and conceptual models of, physical phenomena through the use of visualization in an electricity and magnetism course using web-based technologies (Belcher & Bessette, 2001;Dori et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In active learning approaches for physics education students, one way to teach abstract concepts is the interaction with these concepts through computer-based visualizations or animations, which make unseen phenomena visible and also allow small experiments [9] [13]. Simulations have been shown by Wieman and Perkins as more effective, safe, and cost-efficient compared to traditional experiments [18].…”
Section: Related Workmentioning
confidence: 99%
“…Many studies of retention on other standardized instruments testing conceptual physics knowledge [9][10][11][12] show little or no loss of knowledge over retention intervals ranging from several months to several years. Indeed, this is consistent with our finding that the average score on the MBT among the retest participants is remarkably stable over the interval from the completion of freshman mechanics to graduation.…”
Section: Conclusion a Quantitative Findingsmentioning
confidence: 99%